재가 여성노인의 수면에 영향을 미치는 요인 - 석소현; 최진이; Sok, So-Hyune R; Choi, Jin-Yi (Journal of Korean Academy of Nursing, 2010)
Purpose: The study was done to identify factors influencing the sleep of elderly women. Methods: Data were collected by questionnaires from 203 elderly women in Seoul and Gyeong-gi province. Measures were physical health state, family support, life satisfaction, sleep, depression, and quality of life. Data were analyzed using Pearson correlation coefficients, t-test, ANOVA, and stepwise multiple regression with SPSS/WIN 13.0 version. Results: The mean score for sleep for elderly women was 39.04. Sleep for elderly women according to religion, education level, spouses, and monthly income showed significant differences. Sleep for elderly women showed significantly positive correlations to physical health state, family support, life satisfaction, and quality of life. The significant factors influencing sleep of elderly women were physical health state, family support, depression, and quality of life, which explained about 70.4% of the variance. The strongest factors influencing the sleep was physical health state. Conclusion: The results suggest that in developing nursing interventions and practice for sleep pattern of elderly women spouses and family support should be considered.